Livelihood Option from Minor Forest Produce: Context of Non Timber Forest Product and Poverty Reduction in Mid Hills of Nepal - Acharya, Ganesh Raj; Koirala, Pashupati Nath; Neupane, Laxman; Devkota, Suvas Chandra (Journal of Wetlands Ecology, 2009)
The paper recognizes Non Timber Forest Products (NTFPs) as contributing factor for improving livelihoods of the rural people. Existing trend of NTFPs in Rolpa district reveals high level of its potential where a single Malagiri tree in the one of the VDC of the district has yielded profit of 15, 000 NRs. in gross. The study supports idea that the quality of life can be secured through the promotion of NTFP as an additional crop for safety net. Major outlet clusters for NTFP trade and marketing of the Rolpa district are Sulichaur and Holeri regions where mostly NTFP species were found to be traded. Malagiri, Timur, Ritha and Allo are major local species that have a high level of demand in the market. As a result, people have started cultivating a few species in their farmland too. Lack of knowledge and skill in the production of standard commodity has compelled district people towards traditional NTFP farming approach where they are not reaping optimum benefit. Realizing the potential of NTFPs in the district, it is important to consider modernizing the processing of raw material, development of transportation network and undertake facility for the producers. Such intervention could be a major breakthrough in the poverty reduction of the district and securing quality of life. Key words: NTFP, Livelihood, Community, Marketing DOI: 10.3126/jowe.v2i1.1858 Journal of Wetlands Ecology, (2009) vol. 2, pp 57-66